Addressing antiretroviral therapy-related diagnostic coverage gaps across South Africa using a programmatic approach - Naseem Cassim; Lindi M. Coetzee; Wendy S. Stevens; Deborah K. Glencross (African Journal of Laboratory Medicine, 2018)
Background: A major challenge facing South Africa is the concomitant HIV and tuberculosis epidemics. The National Health Laboratory Service provides testing for staging HIV-positive patients, monitoring patients on antiretroviral therapy (ART) and diagnosing tuberculosis. Not all health districts have equivalent ART-related coverage in particular for CD4 and HIV viral load testing.